2022
DOI: 10.3390/cancers14041055
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Somatostatin Analogues for Diagnosis and Treatment of Neuroendocrine Tumors

Abstract: Neuroendocrine neoplasms (NENs) are rare and heterogeneous tumors that require multidisciplinary discussion for optimal care. The theranostic approach (DOTA peptides labelled with [68Ga] for diagnosis and with 90Y or 177Lu for therapy) plays a crucial role in the management of NENs to assess disease extension and as a criteria for peptide receptor radionuclide therapy (PRRT) eligibility based on somatostatin receptor (SSTR) expression. On the diagnostic side, [68Ga]Ga-DOTA peptides PET/CT (SSTR PET/CT) is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 188 publications
0
8
0
Order By: Relevance
“…TEM and CAPTEM can also be combined with PRRT to improve activity and cover the latency of PRRT effect onset [ 55 ]. Recently, the Australasian Gastrointestinal Trials Group (AGITG) CONTROL NET study, a randomized (2:1) phase II open-label trial of 177Lu-Octreotate PRRT in combination with CAPTEM, enrolled 28 patients with panNET: 19 were randomized to receive CAPTEM + PRRT, while 9 received CAPTEM alone [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…TEM and CAPTEM can also be combined with PRRT to improve activity and cover the latency of PRRT effect onset [ 55 ]. Recently, the Australasian Gastrointestinal Trials Group (AGITG) CONTROL NET study, a randomized (2:1) phase II open-label trial of 177Lu-Octreotate PRRT in combination with CAPTEM, enrolled 28 patients with panNET: 19 were randomized to receive CAPTEM + PRRT, while 9 received CAPTEM alone [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that PET-CT imaging using 68 Ga-labeled somatostatin analogs ( 68 Ga-SSA) as contrast agents exhibit exceptionally high specificity and sensitivity in the diagnosis of NETs [33][34][35]. Additionally, 68 Ga PET/CT can serve as a valuable tool in guiding the management of Peptide Receptor Radionuclide Therapy (PRRT) and Somatostatin Analogues (SSA) [36]. Therefore, it plays a critical role in the comprehensive management of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…According to the European guidelines, SSTR PET is preferred over octreoscan for the diagnostic workup of NETs[ 20 , 21 ]. 18F is the most widely employed radionuclide in PET owing to its chemical, physical, and nuclear properties, which render it ideal for peptide-based imaging[ 22 ]. Despite these advantages, until recently, only a few radiotracers for SSTR labeled with 18F have been described[ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%